Who Does International Law Serve? - M. Mateykovich; A. Skorobogatko (BRICS Law Journal, 2024)
International law is an effective tool for preventing and resolving conflicts between countries, as well as for facilitating their efficient cooperation in the fields of security, trade, and the protection of human rights. With the emergence of interstate bodies that accept appeals from citizens who disagree with the way their interests were protected within the state, the scope of international law has expanded to include not only the states and their peoples (which is why this law is called “international”) but also individuals who can now be considered subjects of international law. However, in recent years, the authority of international law has seriously weakened. The reasons for this are the selective attitudes toward the fulfillment of obligations assumed by individual governments,“double standards” in the application of generally recognized norms and principles to different states, and outright pressure exerted on interstate bodies by countries claiming global hegemony. The authors prove that international law can well regain its former trust and effectively serve its purposes of promoting peace, universal security, and justice. They support their claim by providing examples of such interstate associations as BRICS, the Shanghai Cooperation Organization, and the Eurasian Economic Union, which are based on and successfully operate on the principles of multipolarity, equality, and mutual respect. The article highlights the efforts made by the Russian Federation and the People’s Republic of China aimed at the strict observance of the principles of state sovereignty, human rights, and freedoms, including the right to speak one’s native language, as well as the principles of equality and justice in resolving disputes that arise in international relations.